Potassium Status of Four Rice Growing Soils of Bangladesh (Bangladesh Journal of Agricultural Research, 2012)
Soils of varying K status were selected at the BAU farm, Mymensingh and   BADC farm, Madhupur for conducting laboratory, pot, and field experiments to see the dynamics of potassium in wet land rice soils. The soils were BAU-1(0.087 cmol/kg soil), BAU-2 (0.146 cmol/kg soil), Maddhupur-1 soil (0.097cmol/kg soil), and Madhupur-2 soil (0.706 cmol/kg soil). Almost neutral silt loam soils (Sonatola series) of BAU firm developed on the recent alluvial deposits of Old Brahmaputra Flood Plain and the acidic clayey soils (Noadda and Kalma series) of BADC farm developed on Madhupur clay. The laboratory experiments were potassium release capacity of soils, Q/I relationships of potassium. Results of the experiments showed that BADC farm soils released more K than BAU farm soils. The Q/I relationship showed that the equilibrium exchangeable K (EK0) and labile K (KL) of Madhupur-2 soil were higher than other soils. The potential buffering capacity (PBCK) was higher in BAU-2(5.19±0.12 cmol/kg (mol/L)1/2 soil followed by BAU-1 (4.07±0.09 cmol/kg (mol/L)1/2) and then Madhupur-2 soil (2.23±0.04 cmol/kg (mol/L)1/2). BAU farm soils adsorbed 55 to 60% of added K in non-exchangeable form, while it was 33 to 39% in BADC farm soils.   DOI: http://dx.doi.org/10.3329/bjar.v36i4.11750   Bangladesh J. Agril. Res. 36(4): 633-646, December 2011